Blackwell Publishing Ltd Clinical randomized controlled trial of chemomechanical caries removal (CarisolvÃƒÂ¢Ã¢â‚¬Å¾Ã‚Â¢) - M. A. LOZANO-CHOURIO, O. ZAMBRANO, H. GONZÃƒÆ’Ã‚ÂLEZ, & M. QUERO (Paediatric Dentistry, 2006)
The purpose of this study was to compare the chemomechanical caries-removal system (Carisolv™)with high-speed excavation in cavitated occlusal caries of primary molars.